1980
DOI: 10.1103/physrevb.21.2625
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen location in yttrium dihydride by means of NMR measurements

Abstract: The proton magnetic resonance rigid-lattice second moment in YH, » and YHl 98 has been measured in the temperature range 160-200 K. From these the occupancy factors for hydrogen in the octahedral and tetrahedral interstitial sites of the fcc metal lattice have been determined. A significant fraction ( 10-15%) of the octahedral sites are found to be occupied, consistent with features observed in the optical properties of YH, .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…fluorite structure to the hexagonal structure of nominal YD 3 begins [4]. However, neutron diffraction [20,21] and hydrogen NMR second-moment [22] evidence suggested that O-sites begin to fill well before the T sites are filled (i.e., x < 2).…”
Section: Results In Yd Xmentioning
confidence: 99%
“…fluorite structure to the hexagonal structure of nominal YD 3 begins [4]. However, neutron diffraction [20,21] and hydrogen NMR second-moment [22] evidence suggested that O-sites begin to fill well before the T sites are filled (i.e., x < 2).…”
Section: Results In Yd Xmentioning
confidence: 99%
“…Weaver et al 19 concluded from optical measurements and band-structure calculations that premature octahedral filling occurs in bulk YH x between xϭ1.7 and 1.9. Inelastic neutron scattering, 20 neutron powder diffraction, 21 and nuclear magnetic resonance 22 yielded octahedral fillings of 8 -16 % for bulk YH 2.0 . These results are consistent with the minimum in resistivity at xϭ1.8, observed by Kooij et al 6 for polycrystalline YH x films.…”
Section: A Metal-insulator Transition In La 1àz Y Z H Xmentioning
confidence: 98%
“…On the other hand, Goldstone et al [23] studied the site occupancy of YH2.0 between 15-420 K and demonstrated that octahedral occupancy tended to decrease with increasing temperature, which was contrary to what was expected. Regarding H concentration dependence, Anderson et al [28] notes an O-site occupancy increase from 10.5 to 15.5% in YH1.98 compared to that of YH1.92, as well as hydrogen diffusion rates 3 orders of magnitude higher in YH1.98 than in YH1.63. On the other hand, Stuhr et al report an opposite behavior for TiHx [13], in which increasing x from 1.59 to 1.86 caused the self-diffusion coefficient to decrease.…”
Section: Discussionmentioning
confidence: 99%